PERCEIVED AREAS FOR FUTURE INTERVENTION AND RESEARCH ADDRESSING CONVEYANCE DECISIONS AND POTENTIAL THREATS TO PATIENT SAFETY: STAKEHOLDER WORKSHOPS. Issue 9 (18th August 2016) - O'Hara, Rachel; Johnson, Maxine; Hirst, Enid; Weyman, Andrew; Shaw, Deborah; Mortimer, Peter; Newman, Chris; Storey, Matthew; Turner, Janette; Mason, Suzanne; Quinn, Tom; Shewan, Jane; et al.
Abstract : Background: As part of a study examining systemic influences on conveyance decisions by paramedics and potential threats to patient safety, stakeholder workshops were conducted with three Ambulance Service Trusts in England. The study identified seven overarching systemic influences: demand; priorities; access to care; risk tolerance; training, communication and resources. The aim of the workshops was to elicit feedback on the findings and identify perceived areas for future intervention and research. Attendees were also asked to rank the seven threats to patient safety in terms of their perceived importance for future attention. Methods: A total of 45 individuals attended across all the workshops, 28 ambulance service staff and 17 service user representatives. Discussions were audio-recorded, transcribed and thematically analysed. A paper based paired comparison approach was used to produce an ordinal ranking to illustrate the relative prioritisation of issues. Analysis included testing for internal consistency and between-rater agreement for this relatively small sample. Findings: The two highest ranking priorities were training and development, as well as access to care. The areas for intervention identified represent what attendees perceived as feasible to undertake and relate to: care options; cross boundary working; managing demand; staff development; information and feedback; and commissioning decisions. Perceived areas for research specifically address conveyance decisions and potential threats to patient safety. 17 areas for research were proposed that directly relate to six of the systemic threats to patient safety. Conclusions: Feedback workshops were effective in the validation of findings as well as providing an opportunity to identify priorities for future interventions and research. They also facilitated discussion between a variety of Ambulance Service staff and service user representatives. Ongoing collaboration between members of the research team has enabled some of the research recommendations to be explored as part of a mutually agreed research agenda.